Experiential Value and Novelty Cultivating Brand Love and Behavioral Intentions in Technopreneurship - Setiawan, Sandy; Alma Tiara, Kania; Rustine, Mira; Hilman, Dodi; Joy, Kathleen; Jumbri, Isma Addi (Aptisi Transactions On Technopreneurship (ATT), 2025)
This study explores the influence of experiential value and novelty on customer satisfaction, brand love, and behavioral intention in robot barista coffee shops (RBCS) in Bandung, Indonesia. The research highlights how these variables interact to shape consumer behavior in a novel service setting. Data from 250 respondents, collected using a purposive sampling method and analyzed through Partial Least Squares (PLS), reveal several key findings. Experiential value significantly improves customer satisfaction, emphasizing the importance of engaging and memorable service experiences. Novelty is also a critical driver, contributing to customer interest and satisfaction by offering unique and innovative service encounters. Customer satisfaction strongly affects brand love, indicating that emotional attachment plays a central role in building customer loyalty. Furthermore, satisfied customers are more likely to exhibit positive behavioral intentions, including repeat visits and advocacy. These results underline the necessity for businesses to continuously innovate and enhance service quality to foster long-term customer relationships. This study not only adds to the limited research on robotic services in Indonesia but also offers practical insights for industry stakeholders aiming to adopt innovative technologies in customer-facing roles. Moreover, the findings contribute to the Sustainable Development Goals (SDGs) by advancing innovation (SDG 9) and promoting sustainable consumption patterns (SDG 12). By integrating robotics and prioritizing customer experience, businesses can create sustainable competitive advantages in the evolving service landscape.